BIOACTIVE POTENTIAL OF CULTIVATED MENTHA ARVENSIS L. FOR PRESERVATION AND PRODUCTION OF HEALTH-ORIENTED FOOD - M. Asghar; M. Younas; B. Arshad; W. Zaman; A. Asma; S. Rasheed; A. H. Shah; F. Ullah; S. Saqib (Journal of Animal and Plant Sciences, 2022)
Mentha arvensis L. is traditionally used in folk medicine, and pharmacological industry due to presence of active chemical substances. It is also valuable for food industry as additives because of the presence of antioxidant, cytotoxic, antidiabetic and antimicrobial constituents. This study is intended to examine reactive oxygen species (Cvetanović et al.) generation, lipid oxidation, cytotoxicity and antimicrobial effect of aqueous extract from M. arvensis L. prepared in various solvents i.e. fermented methanol extract (FM.E), distilled water extract (DW.E) and methanol extract (M.E). Phytochemical screening of the extract was qualitatively investigated for the isolation of alkaloids, flavonoids, fats and oils, menthol and quinones. To check the potential of extract as preservative, pH, lipid oxidation and Fourier transformed infrared spectroscopy (FT-IR) analysis was performed. Our results showed FM.E induce ROS generation, cytotoxicity and inhibit Staphylococcus aureus (4.20±0.90 mm) and Pseudomonas aeruginosa (3.23±0.32 mm) growth. In addition, in vivo results showed FM. E and M.E efficiently maintained chicken meat pH and reduced lipid oxidation. The presence of essential phytochemicals was responsible for inhibition of biofilm formation. FT-IR analysis revealed the presence of free OH stretching vibrations at 3878.69 cm-1, free NH at 3459.56 cm-1 and H-NH bond stretching 3388.02 cm-1 groups in chicken meat which belong to M. arvensis L. extracts. These results suggest that menthol from M. arvensis L. extract is favorable food additive against resistant pathogens.
Keywords: Mentha arvensis L; Phytochemicals; ROS generation; Lipid oxidation; Antimicrobial